2002
DOI: 10.1093/jn/132.8.2258
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Reduces Paraquat-Induced Oxidative Stress in Rats

Abstract: The effect of soy protein, soy isoflavones and saponins on paraquat (PQ)-induced oxidative stress was investigated in rats. Rats were fed experimental diets containing casein (CAS), soy protein (SPI), and casein with soy isoflavones and saponins (CAS + IS). The diets were supplemented or not with 0.025% paraquat (CAS + PQ, SPI + PQ, and CAS + IS + PQ). The protective effects of soy protein, soy isoflavones, and saponins on paraquat-induced oxidative stress were examined. Ingestion of soy protein generally miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Dietary soy protein also resulted in lower circulating byproduct of lipid peroxidation (TBAR), hepatic oxidized glutathione, and increased hepatic reduced:oxidized glutathione ratio. This is consistent with previous studies demonstrating antioxidative effects of dietary soy versus milk protein [47, 48]. Despite improvements in cholesterol homeostasis and reduced indices of oxidative stress with soy protein feeding, serum insulin (5 hr fasted) and HbA1c levels were elevated with SPI compared with MPI feeding.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary soy protein also resulted in lower circulating byproduct of lipid peroxidation (TBAR), hepatic oxidized glutathione, and increased hepatic reduced:oxidized glutathione ratio. This is consistent with previous studies demonstrating antioxidative effects of dietary soy versus milk protein [47, 48]. Despite improvements in cholesterol homeostasis and reduced indices of oxidative stress with soy protein feeding, serum insulin (5 hr fasted) and HbA1c levels were elevated with SPI compared with MPI feeding.…”
Section: Discussionsupporting
confidence: 92%
“…Note the signifi cant increase in total plasma testosterone (logarithmic; mean + SD). [20] , enhancing the expression of lipoprotein receptors [21] or (mostly valid for soy protein) decreasing oxidative stress, whether induced [22] or intrinsic [23] . These effects are more profound in diabetic patients [24] , but questionable in healthy perimenopausal women [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we demonstrated in healthy subjects that consumption of a diet enriched with soy containing isoflavones increased high-density lipoprotein concentrations [5] and decreased the concentration of plasma F 2 -isoprostanes compared with consumption of a diet enriched with soy from which the isoflavones had been extracted [6]. The antioxidant properties of soy have also been demonstrated [7], and particularly daidzein has been shown to ameliorate the malondialdehyde (MDA) concentration in the rat [8]. This suggests that phytoestrogens have therapeutic potential to protect against organ injury.…”
Section: Introductionmentioning
confidence: 86%